what is 2(x+4)-5(x-3)=32

Notice: Undefined variable: position6 in /home/domains2/public_html/painphr.com/show.php on line 143

Guide :

# what is 2(x+4)-5(x-3)=32

Need help in solving x in this equation

## Research, Knowledge and Information :

Notice: Undefined variable: go_page in /home/domains2/public_html/painphr.com/show.php on line 211

### Three rules of exponents - A complete course in algebra

... Section 2 Three Rules of Exponents. Back to Section 1. ... Multiply 3x 2 · 4x 5 ... 5 = 32a 10 b 15 : d) (xy 3 z 5) 2 = x 2 y 6 z 10 : e) (5x 2 y 4) ...

### What is (X^(2)) * (X^(1/2))? - Quora

$x^{5/2} = (x^{1/2})^5 = \sqrt{x}^5 ... [math] \sqrt{4}^5 = 2^5 = 32$. You can verify that that's the same as plugging 4 into your original expression:

### 5 Ways to Solve for X - wikiHow

How to Solve for X. There are a number of ways to solve for x, ... 2 2 (4+3)+ 9 - 5 = 32; 2 2 (7) + 9 - 5 = 32; 4(7) + 9 - 5 = 32; 28 + 9 - 5 = 32; 37 - 5 = 32; 32 ...

### Did you solve it? Complete the equation 10 9 8 7 6 5 4 3 2 1 ...

Did you solve it? Complete the equation 10 9 8 7 6 5 4 3 2 1 = 2016 ... (32 and 9) out of (10 9 8) and (6 5 4 3 2 1). If this worked I’d have (10 9 8) x 7 x ...

### (4x-5)^2 = -32 - Math Central

(4x-5)^2 = -32 . Hi Tracey, You could ... Whenever I do this kind of algebra, I like to check my answer by putting it in for x in the original equation: (4x-5) 2 =(4 ...

### How to solve for $x$ in $x^2=16^x$ - Quora

$$$\begin{split}x^2&=16^x\\ \implies |x|&=4^x\end{split}$$\tag*{}$ [math]\text{Case I:}\\ \begin{split}x&=4^x ...

### Untitled Document [www.math.brown.edu]

(x 2 + 4x - 1)(x 3 - 2x 2 + 4) = x 5 - 2x 4 + 4x 2 + 4x 4 - 8x 3 + 16x - x 3 + 2x 2 - 4 (x 2 + 4x - 1)(x 3 - 2x 2 + 4) = x 5 + 2x 4 - 9x 3 + 6x 2 + 16x - 4. Factoring ...

### 15/32 in. x 4 ft. x 8 ft. 3-Ply RTD Sheathing - The Home Depot

15/32 in. x 4 ft. x 8 ft. 3-Ply RTD Sheathing Questions - page 2; y_2017, m_6, d_25, h_6CST; ... The Home Depot Canada; The Home Depot México; Blinds.com; Pro Referral

### Solving an Equation - Avvanta

Solving an Equation Here is a typical equation: 3X - 5 = 27 ... X = 6: Because 3 times 6 = 18: X/4 = 5: If you divide my number by 4, you get 5. What is my number? X ...

### 1/32 = .03125 1/16 = .0625 3/32 = .09375 1/8 = .125 5/32 ...

5/32 = .15625 3/16 = .1875 7/32 = .21875 1/4 = .25 9/32 = .28125 5/16 = .3125 11/32 = .34375 3/8 = .375 13/32 = .40625 7/16 = .4375 15/32 = .46875 1/2 = .5 17/32 = .53125

## Suggested Questions And Answer :

Notice: Undefined variable: position4 in /home/domains2/public_html/painphr.com/show.php on line 277

### f(x)=2x4-x3

f(x) = 2x^4 - x^3 f'(x) = 8x^3 - 3x^2 Setting the derivative to zero, we have: f'(x) = 0 8x^3 - 3x^2 = 0 x^2(8x - 3) = 0 x^2 = 0 or 8x - 3 = 0 x = 0 or x = 3 / 8 Thus, the critical values we have are x = 0 and x = 3 / 8. Now, we will draw a number line with 0 and 3/8 on it. By random substitution

Notice: Undefined variable: position4 in /home/domains2/public_html/painphr.com/show.php on line 277

### find all rational and non-rational zeros P(x)=2x^4 + 5x^3 − 5x^2 − 5x + 3

P(x) = 2x4 + 5x3 - 5x2 - 5x +3 ⇒P(1) = 2 + 5 - 5 - 5 + 3 = 0 ⇒ x - 1 is a factor ⇒P(-1) = 2 - 5 - 5 + 5 + 3 = 0 ⇒ x + 1 is a factor ⇒(2x4 + 5x3 - 5x2 - 5x +3)/(x2 - 1) = 2x2 + 5 x - 3 ⇒ (x2 - 1)(2x2 + 5 x - 3) = (x + 1)(x - 1)(2x - 1)(x + 3) = 0 ⇒ x = -3, -1, ½, 1

Notice: Undefined variable: position4 in /home/domains2/public_html/painphr.com/show.php on line 277

### how do I fiqure this out 2x4^3x=8x/16

The right-hand side can be simplified to x/2. By doubling, we can get rid of the fraction: 4x4^3x=x. Assuming this is meant to be: 4x(4^3x)=x then we have x(4*4^3x-1)=0 and x=0 is a solution. The other solution is 4^3x=1/4. Take logs to the base 4: 3x=-1 so x=-1/3. Alternatively, we can w

Notice: Undefined variable: position4 in /home/domains2/public_html/painphr.com/show.php on line 277

### BET you cant answer this! ~~~HELP~~~

None of the graphs match the pictures. The first equation contains the point (0,42), which does not appear on any of the graphs. The second equation contains the point (1,9), which does not appear on any of the graphs. The third equation contains the point (0,-8), which does not appear on any of

Notice: Undefined variable: position4 in /home/domains2/public_html/painphr.com/show.php on line 277

### solve the equations

Notice: Undefined variable: position4 in /home/domains2/public_html/painphr.com/show.php on line 277

### Find the pts on the graph of z=xy^3+8y^-1 where the tangent plane is parallel to 2x+7y+2z=0.

Question: Find the pts on the graph of z=xy^3+8y^-1 where the tangent plane is parallel to 2x+7y+2z=0. The tangent plane to the surface z=f(x,y)=xy^3+8/y is given by 2x+7y+2z=D Where D is some constant. The equation of the tangent plane to the surface f(x,y), at the point (x_0 y_0 ) ca

Notice: Undefined variable: position4 in /home/domains2/public_html/painphr.com/show.php on line 277

### what are the possible combination of making 30 with 1, 3, 5, 7, 9

I started off by figuring how many ways to use nines: 30   3 nines, 27 total   2 nines, 18 total   1 nine, 9 total   0 nines, 0 total I then figured how many ways to use sevens: 30   3 nines, 27 total     0 sevens, 27 total &nb

Notice: Undefined variable: position4 in /home/domains2/public_html/painphr.com/show.php on line 277

### What is inverse

If B= ( b 0 0 ) ( 0 b 0 ) = bI, where I is the identity matrix, ( 0 0 b ) then B^7= ( b^7 0 0 ) ( 0 b^7 0 ) = ( 0 0 b^7 ) So  ( b^7 0 0 )   ( 3b 0 0 )    ( 1 0 0 )    ( 0 0 0 ) ( 0 b^7 0 ) - ( 0 3b 0 ) + ( 0 1 0 ) = ( 0 0 0 ). ( 0 0 b^7

Notice: Undefined variable: position4 in /home/domains2/public_html/painphr.com/show.php on line 277

(1) I am assuming this is not a calculus question where dx, dy and dz have a different meaning. Variable d can be removed as a common factor: ax/((b-c)yz)=by/((c-a)zx)=cz/((a-b)xy) Take the first pair and remove common factor z: ax/((b-c)y)=by/((c-a)x); ax^2(c-a)=by^2(b-c); ax^2=by^2(b-c

Notice: Undefined variable: position4 in /home/domains2/public_html/painphr.com/show.php on line 277

### how do you solve this using a gausian reduction using the three equations? 4x+z=3,2x-y=2,and 3y+2z=0

how do you solve this using a gausian reduction using the three equations? 4x+z=3,2x-y=2,and 3y+2z=0 I think gaussian reduction is similar to back substitution, but with all the equation shaving different variables... just not sure how to do it. You create a matrix using the constants in the equati

#### Tips for a great answer:

- Provide details, support with references or personal experience .
- If you need clarification, ask it in the comment box .
- It's 100% free, no registration required.
next Question || Previos Question

Notice: Undefined variable: position5 in /home/domains2/public_html/painphr.com/show.php on line 357
• Start your question with What, Why, How, When, etc. and end with a "?"
• Be clear and specific
• Use proper spelling and grammar